2016
DOI: 10.1038/nphoton.2016.174
|View full text |Cite
|
Sign up to set email alerts
|

Sub-cycle optical phase control of nanotunnelling in the single-electron regime

Abstract: The high peak electric fields provided by single-cycle light pulses can be harnessed to manipulate and control charge motion in solid-state systems, resulting in electron emission out of metals and semiconductors [1][2][3][4][5][6] or high harmonics generation in dielectrics 7,8 . These processes are of a non-perturbative character and require precise reproducibility of the electric-field profile 9-14 . Here, we vary the carrier-envelope phase of 6-fs-long near-infrared pulses with pJ-level energy to control e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
171
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(178 citation statements)
references
References 29 publications
1
171
0
Order By: Relevance
“…An added value of this line of research is that attosecond pulses also enable damage-free exposure of insulating solids to electric fields of the order of the Zener critical field F crit = E g /ea. Ultra-rapid reversible optical waveforms were shown to increase the a.c. conductivity of wide-bandgap dielectrics by more than 18 orders of magnitude within 1 femtosecond 13,122 . These experiments open pathways for signal processing in the petahertz domain, which is not attainable with common electronics.…”
Section: Phononic Controls Of Quantum Materialsmentioning
confidence: 99%
“…An added value of this line of research is that attosecond pulses also enable damage-free exposure of insulating solids to electric fields of the order of the Zener critical field F crit = E g /ea. Ultra-rapid reversible optical waveforms were shown to increase the a.c. conductivity of wide-bandgap dielectrics by more than 18 orders of magnitude within 1 femtosecond 13,122 . These experiments open pathways for signal processing in the petahertz domain, which is not attainable with common electronics.…”
Section: Phononic Controls Of Quantum Materialsmentioning
confidence: 99%
“…It has been shown that the energyresolved spectra of photo-emitted electrons in the regime close to the cutoff energy are strongly modulated by the CEP, which can be used to retrieve the position-resolved absolute phase of a laser beam [70]. More recently, experiments have shown that the total electron yield from a single junction [105] or from an array of nanostructures [106] is also CEP dependent, see Fig. 3.…”
Section: Ultrafast Currents From Nanostructures and Applicationsmentioning
confidence: 99%
“…electric fields in the hundreds of terahertz regime, can control electron motion around solid-state nanostructures. Most notably, carrier-envelope-phase-sensitive (CEP-sensitive) effects have been observed in photoemission currents from metallic nano-tips [1,2] and, more recently, from metallic nanoparticles [3,4]. Here, we report measurements of CEP-sensitive photoemission from plasmonic nanoparticles driven by few-cycle laser pulses of variable intensity.…”
mentioning
confidence: 94%